2009
DOI: 10.1016/j.molcel.2009.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the WAVE Complex by Coincident Signals Controls Actin Assembly

Abstract: Summary WAVE proteins link upstream signals to actin nucleation by activating the Arp2/3 complex and are at the core of regulatory pathways driving membrane protrusion. They are found in heteropentameric complexes whose role in regulating WAVE function is presently unclear. Here we demonstrate that purified native WAVE complexes are basally inactive; previous reports of constitutive activity are artifacts of in vitro manipulation. Further, the native complexes are not activated by Rac alone. Activation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
320
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(327 citation statements)
references
References 39 publications
6
320
1
Order By: Relevance
“…Previous studies have already shown the importance of these molecules in immune cell chemotaxis (54)(55)(56). For instance, macrophage migration toward CSF-1 requires the Wave2 complex and its phosphorylation by MAPKs because the reduction of its expression through iRNA abrogated F-actin-rich membrane protrusions (54).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already shown the importance of these molecules in immune cell chemotaxis (54)(55)(56). For instance, macrophage migration toward CSF-1 requires the Wave2 complex and its phosphorylation by MAPKs because the reduction of its expression through iRNA abrogated F-actin-rich membrane protrusions (54).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Arf1 has been found to cooperate with Rac1 in activating the WRC (Koronakis et al, 2011). Another layer of activation involves the binding of phosphatidylinositol (3,4,5)-trisphosphate [PI(3,4,5)P 3 ] to the WAVE BR and phosphorylation of WAVE, which can further increase their activity toward Arp2/3 (Lebensohn and Kirschner, 2009). Through these interactions, the WRC can become activated at membranes where it promotes lamellipodia formation, thereby driving cell migration, metastasis and invasion in multiple tumor models (Burianek and Soderling, 2013).…”
Section: Jmymentioning
confidence: 99%
“…Furthermore, biochemical assays of Arabidopsis W/SRC El-Assal et al, 2004;Frank et al, 2004;Le et al, 2006;Uhrig et al, 2007) and ARP2/ 3 assembly (Kotchoni et al, 2009) have shown that the binary interactions among W/SRC subunits and ARP2/3 complex assembly mechanisms are indistinguishable from those that have been observed for human W/SRC (Gautreau et al, 2004) and yeast ARP2/3 (Winter et al, 1999). After an initial period of controversy concerning the biochemical control of W/SRC, it is now apparent that vertebrate W/SRC (Derivery et al, 2009;Ismail et al, 2009), like the ARP2/3 complex (Machesky et al, 1999), is intrinsically inactive and requires positive regulation by Rac and other factors to fully activate ARP2/3 (Ismail et al, 2009;Lebensohn and Kirschner, 2009;Chen et al, 2010). Although overexpression of dominant negative ROP mutants causes trichome swelling and a reduced trichome branch number (Fu et al, 2002), the involvement of ROPs in trichome morphogenesis has been difficult to prove with a loss-offunction ROP allele because so many ROPs are expressed in this cell type (Marks et al, 2009).…”
mentioning
confidence: 91%
“…In mammalian cells that crawl on a solid substrate, current models propose that a cytosolic pool of inactive WAVE/ SCAR proteins and W/SRC is locally recruited and activated at specific plasma membrane surfaces in response to signals from some unknown Rac guanine nucleotide-exchange factor (GEF), protein kinase, and/ or lipid kinase (Oikawa et al, 2004;Lebensohn and Kirschner, 2009;Chen et al, 2010). However, in Drosophila melanogaster neurons (Bogdan and Klämbt, 2003) and cultured human melanoma cells (Steffen et al, 2004), there are large pools of W/SRC with a perinuclear or organelle-like punctate localization that has no obvious relationship to cell shape or motility, raising uncertainty about the cellular mechanisms of W/SRC activation and the importance of different subcellular pools of the complex.…”
mentioning
confidence: 99%